(untitled) (Jurnal Bina Praja, 2021)
Public service is an important issue for the sustainability of a city. To create excellent service, supporting cities such as South Tangerang and other cities are required to develop smart cities as a new way to serve the community. This study aims to further examine regional innovation policies in encouraging regional competitiveness in South Tangerang City. This research used qualitative descriptive research methods. The descriptive research method is used to describe regional innovation policies in South Tangerang City as a unit of analysis based on the facts as they are. The data collection technique in this study uses interview techniques by collecting information from various stakeholders such as government officials, executive and legislative ranks, Businesses/MSME actors, and communities involved in implementing innovation to improve regional heads and regional competitiveness in South Tangerang City. This study concludes that the implementation of regional innovation policies in South Tangerang has not been maximized. In addition to the quality of human resources, several agencies have not been creative in creating innovations. It can be seen from the control of innovation held by the mayor as the regional head. Furthermore, the role of the Regional Head in implementing innovation to improve regional performance and competitiveness is very important, considering that leaders must be able to leverage the knowledge management movement in government organizations so that organizational knowledge development can be executed into much-needed innovation. Recently, the South Tangerang City Government needed to implement the RAJADO model (Replication, Authority, Innovation Network, Budget, and Digitalization/Online).